Percepção ambiental: uma perspectiva fenomenológica na identificação dos problemas ecossistêmicos da comunidade da Maré do Apicum no bairro Coroa do Meio - Aracaju (SE) - Nascimento, Márcio Menezes do (2023)
This research was produced through a systematic bibliographic review on the use of environmental perception from a phenomenological approach to studies of environmental themes. It is from this approach that we analyze the set of experiences and their meanings, highlighting the identification of socio-environmental problems that involve the communities of Maré do Apicum, in the Coroa do Meio neighborhood, in Aracaju (SE). To flesh out the research, readings published in databases, virtual libraries, repositories, platforms, etc. were carried out. Furthermore, we use methodological techniques in accordance with the approach to the phenomena of consciousness, hence the use of photos, the community dimension of the problems. These elements aim to strengthen our argument and highlight the fundamental idea of Environmental Perception, which serves as a basis for establishing a way of understanding reality. By combining data collection with a phenomenological approach that emphasizes environmental perception, we were able to create an E-book as a technical educational product. This technical product portrays the reality experienced in the Maré do Apicum region, with the aim of contributing to the process of environmental and heritage education.